Leading virtual teams : expert solutions to everyday challenges. - Harvard Business School. Press (Boston, Mass. : Harvard Business Press, 2010)
"How do you lead a team scattered across the globe? How do you keep members you can't see organized, communicative, and productive? In this book, you'll find valuable advice on forming virtual teams, assessing their communication and technology needs, and ensuring that they produce high-quality work. You'll learn how to: (1) Understand the benefits and challenges of virtual teams, (2) Build a virtual community that promotes collaboration and ongoing communication, (3) Utilize technology to enhance your virtual team's focus, motivation, and output. Meet Your Mentors: Jessica Lipnack and Jeffrey Stamps are CEO and Chief Scientist, respectively, of the Boston-based consulting firm NetAge and authors of many books and articles on networked organizations, including Virtual Teams."--Publisher's website.
Leading virtual teams: the basics. Why virtual teams? ; Setting the stage for success in your virtual team ; Fostering team identity ; Keeping team members aligned through communication ; Using coaching to enhance team performance ; Leveraging technology effectively. -- Tips and tools. Tools for leading virtual teams ; Test yourself ; To learn more ; Sources for leading virtual teams.
Includes bibliographical references.
Description based on print version record.
Keywords: Virtual work teams -- Management; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books